Implementasi Model Fungsi Transfer dan Neural Network untuk Meramalkan Harga Penutupan Saham (Close Price) - Nila Rahmawati; Trianingsih Eni Lestari (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
The multivariate forecasting model is a model of forecasting that takes into the causal relationship between a prediction factor with one or more independent variables. This study uses multivariate forecasting model that are transfer function and neural network model. The transfer function and neural network model are used for forecasting of closing stock price data by considering the opening stock price data as the independent variable in the forecasting model. The data used in this study is the monthly closing stock price and opening stock price data of PT. Bank Central Asia, Tbk. The best model for forecasting of closing stock price is a transfer function model that has MSE, MAPE, and MAE values ??smaller than the neural network model. Keywords: transfer function, neural network, opening stock price, closing stock price